Tumor-associated CD8+T cell tolerance induced by erythroid progenitor cells - Fan, Xue; Peng, Han; Wang, Xuesong; Sun, Yixin; Dong, Yan; Zhou, Jie; Chen, Jianfang; Huang, Shuo (Frontiers in Immunology, 2024)
Introduction CD8+T cell tolerance plays an important role in tumor escape. Recent studies have shown that CD45+ erythroid progenitor cells (CD45+EPCs) generated through splenic extramedullary erythropoiesis suppress tumor immunity. However, the mechanism underlying how CD45+EPCs mediate CD8+T cell tolerance remains incompletely understood and requires further research. Methods In this study, the antigen-processing abilities of CD45+EPCs was verified through both in vitro and in vivo experiments. We have used the method of co-culture in vitro and adoptive transfer experiments in vivo to explore the effects of CD45+EPCs on CD8+T cell tolerance. RNA-sequencing analysis and blocking experiments were used to evaluate the role of ROS in the CD45+EPC mediated tolerance of CD8+T cells. Finally, we incorporated uric acid into the adoptive transfer experiments to rescue the CD45+EPC mediated tumor-promoting effect. Results and discussion We found that CD45+EPCs take up soluble proteins, present antigenic epitopes on their surface, and induce antigen-specific CD8+T cell anergy. In addition, we found that CD45+EPC directly nitrates tyrosine within the TCR/CD8 complex via the production of reactive oxygen species and peroxynitrite, preventing CD8+ T cells from responding to their specific peptide antigens. Furthermore, uric acid treatment effectively abolished the immunosuppressive effects of CD45+EPCs during CD8+T cell adoptive transfer, thereby enhancing the anti-tumor efficacy. These results demonstrated that CD8+T cell tolerance in tumor-bearing mice is induced by CD45+EPCs. The results of this study have direct implications for tumor immunotherapy.